Večletni potek površinske temperature morske vode v vzhodnem delu Tržaškega zaliva (dejavniki, ki največ vplivajo na termalne vrednosti) - Bićanić, Zlatimir (Geografski vestnik, 1996)
Based on the influence of the following climatic parameters, solar radiation, air temperature and wind, the surface sea temperatures over the period of 40 years have been analysed. The purpose of the research was to confirm or deny the premise that the surface sea tempratures significantly changed, i.e. dropped, in the last few decades. The analysis is based on the temperature data of the 40-year period, and offers the well-founded results.
Keywords: Adriatic Sea; fizična geografija; Gulf of Trieste; hidrogeografija; Jadransko morje; morska voda; physical geography; temperatura; Tržaški zaliv